2019
DOI: 10.1039/c9tb01653h
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Au aerogels with {110}-rich facets by size-dependent surface reconstruction for enzyme-free glucose detection

Abstract: Au6–50 aerogels with {110}-rich facets (35.5%) are fabricated for glucose detection by size-dependent surface reconstruction between two differently-sized gold nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…The Au aerogels with exposed (110) facets were developed to construct the enzyme-free glucose biosensors because the literature reported that the (110) facet of Au NPs is more active for glucose oxidation. 49 By taking advantage of the facet engineering, the optimized Au aerogels with the largest ratio of (110) facets displayed the splendid catalytic activity, reproducibility, and long-term stability for glucose detection with the 2 s response time, a high sensitivity (2044.71 mA cm −2 mM −1 ), and an ultralow LOD (0.58 mM). These works suggested the NMAs are promising candidates for electrochemical biosensors.…”
Section: Applicationsmentioning
confidence: 99%
“…The Au aerogels with exposed (110) facets were developed to construct the enzyme-free glucose biosensors because the literature reported that the (110) facet of Au NPs is more active for glucose oxidation. 49 By taking advantage of the facet engineering, the optimized Au aerogels with the largest ratio of (110) facets displayed the splendid catalytic activity, reproducibility, and long-term stability for glucose detection with the 2 s response time, a high sensitivity (2044.71 mA cm −2 mM −1 ), and an ultralow LOD (0.58 mM). These works suggested the NMAs are promising candidates for electrochemical biosensors.…”
Section: Applicationsmentioning
confidence: 99%
“…Wang et al prepared PtSn alloy aerogels by the wet chemical method. The high density of defects between the nanoparticles in the aerogel structure improves the intrinsic activity of active sites [50]. Similar defect structures have been discovered in many research studies about aerogels, but no one has quantitatively studied the effect of defects on electrocatalysis.…”
Section: Other Structuresmentioning
confidence: 57%
“…Motivated by the urgency of human social and environmental issues, research on novel and advanced metallic nanomaterials for catalysis, electronics, and optics has attracted intensive attention from both academic and industrial communities. Regarding the structural configuration of materials at the nanoscale, the interlocked monomeric particles in three-dimensional metallic nanonetworks (3D-MNWs) lead to many advantageous properties, such as high structural stability, large surface area, and excellent thermal and electronic conductivity, providing great promise for potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…This result implies that nanobubble has a possibility to act as stabilizer, like the surfactant, to stabilize the nanoparticles in aqueous solution. Usually, the 3D-MNWs are synthesized by destabilizing a colloidal solution containing metallic nanoparticles, followed by an aging process. , The destabilization of the colloidal nanoparticles should be fine controlled to ensure the occurrence of destabilization, while also avoiding overwhelming agglomeration of nanoparticles. Considering that the nature of the interaction (a surface strain effect on the nanoscale that happens on the gas–solid–liquid three-phase interface) between nanobubbles and nanoparticles is a weak physical force rather than a strong chemical binding, it is speculated that nanobubble may act as a proper protective agent or template to construct 3D-MNWs without a secondary destabilizing process.…”
Section: Introductionmentioning
confidence: 99%